2015
DOI: 10.1128/aem.01853-15
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Inactivation of Rotaviruses: Role of Treatment Temperature and Strain Diversity in Virus Inactivation

Abstract: c Rotavirus (RV) is the major etiological agent of acute gastroenteritis in infants worldwide. Although high-pressure processing (HPP) is a popular method to inactivate enteric pathogens in food, the sensitivity of different virus strains within same species and serotype to HPP is variable. This study aimed to compare the barosensitivities of seven RV strains derived from four serotypes (serotype G1, strains Wa, Ku, and K8; serotype G2, strain S2; serotype G3, strains SA-11 and YO; and serotype G4, strain ST3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…46 Other direct antiviral methods may physically destroy/ break viral capsid, such as high pressure, radiation, and the action of some nanoparticles. [47][48][49][50] The photodynamic inactivation (PDI) as an antiviral approach exploits the function of photosensitizers under light illumination to generate ROS to attack viral envelope lipids, core proteins, capsid, and nucleic acid, leading to the loss of virus infectivity. 51 CDots due to their unique photoexcited state properties and processes represent a new class of particularly effective PDI agents, as already demonstrated in their visible/natural light-activated actions against bacterial cells, are expected to be similarly effective antiviral PDI agents (Fig.…”
Section: Bacteriophage Infection and Antiviral Strategiesmentioning
confidence: 99%
“…46 Other direct antiviral methods may physically destroy/ break viral capsid, such as high pressure, radiation, and the action of some nanoparticles. [47][48][49][50] The photodynamic inactivation (PDI) as an antiviral approach exploits the function of photosensitizers under light illumination to generate ROS to attack viral envelope lipids, core proteins, capsid, and nucleic acid, leading to the loss of virus infectivity. 51 CDots due to their unique photoexcited state properties and processes represent a new class of particularly effective PDI agents, as already demonstrated in their visible/natural light-activated actions against bacterial cells, are expected to be similarly effective antiviral PDI agents (Fig.…”
Section: Bacteriophage Infection and Antiviral Strategiesmentioning
confidence: 99%
“…It has been shown that the resistance of viruses to pressure changes greatly, is largely determined by their structure [29], and is related to the taxonomic groups or even strains, and the temperature applied during pressurization [85]. Enveloped viruses are usually more sensitive to pressure treatments than naked viruses.…”
Section: Effects On Microorganisms and Virusesmentioning
confidence: 99%
“…There are numerous RV strains, and it is not financially or time‐wise possible to conduct risk assessments for all the strains. Thus, to make a representative and conservative scenario for RV, we have chosen RV strain OSU, which is known as one of the most resistant RV strains (Araud et al., ; Araud, Shisler, & Nguyen, ; Fuzawa, Araud, Li, Shisler, & Nguyen, ; Romero‐Maraccini et al., ).…”
Section: Methodsmentioning
confidence: 99%